Desenvolvimento de linhagens geneticamente modificadas por CRISPR/CAS9 na identificação de moléculas alvos para genes C-MYC, TRP53 e H19 - Santos, Renan da Silva (2018)
Cancer is a disease of heterogeneous genetic and epigenetic aspects. Knowing the demand for more specific treatments to the molecular subtypes, different tools for identifying targets of anticancer agents are required. The discovery of genome-editing technologies has leveraged different lines of research, most recently the CRISPR/Cas9 system has further facilitated genetic manipulation. The use of the CRISPR/Cas9 platform for the generation of in vitro models that could facilitate the identification of molecules and their respective targets can represent an important step in the treatment of cancer. In this work, we aimed to develop genetically modified murine cell lines. The editions comprise: T58A point mutation in the c-Myc gene; Trp53 knockout; deletion of the H19 promoter. Genes were evaluated through the Genbank database and the most appropriate sequences were used for RNA guide designs by the CRISPR design platform. We used the vector px458 that presents in its constitution the components for the machinery of CRISPR / Cas9, which was digested initially by the enzyme BbsI. Upon binding of the gRNAs in their respective vectors (px458-c-Myc, px458-Trp53, px458Up-H19, px458Down-H19), they were transformed and cloned into TOP10 competent bacteria (E. coli). After cloning, vectors were transfected into murine C2C12 non-tumor lines and plasmid DNA was extracted. The editing region was amplified to finally have its validation confirmed by the enzymatic matching recognition assay of the T7 endonuclease enzyme. The results of the bands patterns observed in agarose gel obtained of the T7 digestion validate the editing ability of the four vectors developed. For reasons of results, the H19 deletion lineage was selected to continue the work. Of 76 colonies newly transfected with wings px458Up-H19, px458Down-H19, a deletion confirmed by sequencing.SAN